A Hands-On Course in Sensors Using the Arduino and Raspberry Pi - Ziemann, Volker (Boca Raton, FL : CRC Press, 2018)
"A Hands-On Course in Sensors using the Arduino and Raspberry Pi is the first book to give a practical and wide-ranging account of how to interface sensors and actuators with micro-controllers, Raspberry Pi and other control systems. The author describes the progression of raw signals through conditioning stages, digitization, data storage and presentation.The collection, processing, and understanding of sensor data plays a central role in industrial and scientific activities. This book builds simplified models of large industrial or scientific installations that contain hardware and other building blocks,including services for databases, web servers, control systems, and messaging brokers. A range of case studies are included within the book, including a weather station, geophones, a water-colour monitor, capacitance measurement, the profile of laser beam, and a remote-controlled and fire-seeking robotThis book is suitable for advanced undergraduate and graduate students taking hands-on laboratory courses in physics and engineering. Hobbyists in robotics clubs and other enthusiasts will also find this book of interest."--Provided by publisher.
chapter 1 Introduction / Volker Ziemann -- chapter 2 Sensors / Volker Ziemann -- chapter 3 Actuators / Volker Ziemann -- chapter 4 Microcontroller: Arduino / Volker Ziemann -- chapter 5 Host Computer: Raspberry Pi / Volker Ziemann -- chapter 6 Control System: EPICS / Volker Ziemann -- chapter 7 Messaging System: MQTT / Volker Ziemann -- chapter 8 Example: Weather Station with Distributed Sensors / Volker Ziemann -- chapter 9 Example: Geophones / Volker Ziemann -- chapter 10 Example: Monitor for the Color of Water / Volker Ziemann -- chapter 11 Example: Capacitance Measurement / Volker Ziemann -- chapter 12 Example: Profile of a Laser Beam / Volker Ziemann -- chapter 13 Example: Fire-Seeking Robot / Volker Ziemann -- chapter 14 Presenting and Writing / Volker Ziemann.
Keywords: Electric testing; Electronic instruments; Measurement; Physics; Robotics; Applied Physics; COMPUTERSCIENCEnetBASE; ElectricalEngineeringnetBASE; ENGnetBASE; INFORMATIONSCIENCEnetBASE; Instrumentation, Measurement & Testing; PHYSICSnetBASE; Robotics; SCI-TECHnetBASE; STMnetBASE